Evidence-Based Approaches for the Treatment of Maltreated Children Considering core components and treatment effectiveness - Timmer, Susan; Urquiza, Anthony; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This volume provides an overview of the research describing the effects of child maltreatment on mental health, cognitive and social-emotional development. It offers descriptions of selected empirically based treatments (EBTs) written by scholars associated with its development, training, or research on its effectiveness. Each contributor presents the theoretical foundation of the EBT and evidence of its efficacy, describes the treatment process and illustrates this process with a case study of its use with a maltreated child, and discusses possible limitations. Following the chapters describing the interventions, the editors address key issues of the dissemination and implementation of these EBTs. They describe the strategies the selected interventions have used to ensure treatment fidelity in training and dissemination from the perspective of implementation science s core components of implementation. The challenges of implementing EBTs, and the difficulty of fitting protocol to the reality of clinical practice in community mental health settings are also discussed. This volume offers a central source of information for students and practitioners who are seeking effective interventions to address problems associated with child maltreatment.
PART I. INTRODUCTION -- Chapter 1: A Brief History of Identifying Child Maltreatment; Nicole Hollis -- Chapter 2: A Brief History of Evidence-Based Practices; Lindsay A. Forte, Susan G. Timmer and Anthony J. Urquiza -- Chapter 3: Why we think we can make things better with Evidence Based Practices: Theoretical and Developmental Context; Susan G. Timmer -- PART II. INTERVENTIONS FOR INFANTS AND TODDLERS -- Chapter 4: Attachment and Biobehavioral Catch-up: An Intervention for Parents at Risk of Maltreating Their Infants and Toddlers; Mary Dozier, E. B. Meade and Kristen Bernard -- Chapter 5: Child-Parent Psychotherapy with Infants and Very Young Children; Patricia Van Horn and Vilma Reyes -- PART III. INTERVENTIONS YOUNG CHILDREN -- Chapter 6: Incredible Yearsâ Parent and Child Programs for Maltreating Families; Carolyn Webster-Stratton -- Chapter 7: The Importance of Evidence-Based Parenting Intervention to the Prevention and Treatment of Child Maltreatment; Matthew R. Sanders and John A. Pickering -- Chapter 8: Parent Child Interaction Therapy for Maltreated Children; Anthony J. Urquiza and Susan G. Timmer -- Chapter 9: Multidimensional Treatment Foster Care For Preschoolers: A Program for Maltreated Children in the Child Welfare System; Kathryn S. Gilliam and Philip A. Fisher -- PART IV. INTERVENTIONS FOR MIDDLE CHILDHOOD -- Chapter 10: Trauma-Focused Cognitive-Behavioral Therapy; Anthony P. Mannarino, Judith A. Cohen and Esther Deblinger -- Chapter 11: Alternatives for Families: A Cognitive Behavioral Therapy: An Overview and Case Example; David J. Kolko, Heather Simonich and Anna Loiterstein -- PART V. INTERVENTIONS FOR ADOLESCENTS -- Chapter 12: MST-CAN: An Ecological Treatment for Families Experiencing Physical Abuse and Neglect; Cynthia Cupit Swenson and Cindy M. Schaeffer -- Chapter 13: Dialectical Behavior Therapy for Suicidal and Self-Harming Adolescents with Trauma Symptoms; Michele Berk, Janine Shelby, Claudia Avina and Keegan Tangeman -- PART VI. DISSEMINATING EVIDENCE-BASED PRACTICES -- Chapter 14: Taking it to the Street: Disseminating Evidence-Based Practices; Susan G. Timmer and Anthony J. Urquiza -- Chapter 15: The Bridge from Research to Practice- Just Leap across the Last Bit; Susan G. Timmer and Anthony J. Urquiza.
Keywords: Philosophy (General).; Maternal and infant welfare; Psychotherapy; Quality of Life; Quality of Life -- Research; Psychology, clinical; Applied psychology; Developmental psychology; Psychology; Psychotherapy and Counseling; Quality of Life Research; Maternal and Child Health; Psychotherapy; Child and School Psychology; Clinical Psychology